2020
DOI: 10.3390/cells9020465
|View full text |Cite
|
Sign up to set email alerts
|

The Vacuolar H+ ATPase α3 Subunit Negatively Regulates Migration and Invasion of Human Pancreatic Ductal Adenocarcinoma Cells

Abstract: Increased metabolic acid production and upregulation of net acid extrusion render pH homeostasis profoundly dysregulated in many cancers. Plasma membrane activity of vacuolar H+ ATPases (V-ATPases) has been implicated in acid extrusion and invasiveness of some cancers, yet often on the basis of unspecific inhibitors. Serving as a membrane anchor directing V-ATPase localization, the a subunit of the V0 domain of the V-ATPase (ATP6V0a1-4) is particularly interesting in this regard. Here, we map the regulation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 67 publications
(143 reference statements)
0
12
0
Order By: Relevance
“…Besides its plasmalemmal localization, V‐ATPase is also overexpressed in different types of cancer cells 83,91,99–101 . Indeed, we showed that V‐ATPase is overexpressed in highly metastatic cancer cells derived from osteosarcoma, breast and prostate cancer, which is associated with higher extracellular acidification rate and more acidic lysosomes 82,102 .…”
Section: V‐atpases: Attractive Targets For a Multitude Of Human Diseasesmentioning
confidence: 87%
“…Besides its plasmalemmal localization, V‐ATPase is also overexpressed in different types of cancer cells 83,91,99–101 . Indeed, we showed that V‐ATPase is overexpressed in highly metastatic cancer cells derived from osteosarcoma, breast and prostate cancer, which is associated with higher extracellular acidification rate and more acidic lysosomes 82,102 .…”
Section: V‐atpases: Attractive Targets For a Multitude Of Human Diseasesmentioning
confidence: 87%
“…Besides, transcripts ENST00000524816.7 and ENST00000471245.1 were respectively noncoding regions of gene TRIM29 and CKS1B, which were responsible for breast cancer proliferation, metastasis and invasion (26,27). ENST00000587299.1 and ENST00000553238.5 participated in the transcription of gene SLC8B1 and ATP6V0A1 that was associated with the invasive process of oral tongue cancer and pancreatic ductal adenocarcinoma, respectively (28,29). Therefore, lncRNAs may be the vital ingredients in the process of adipocytes induced progression of breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely believed that at high concentrations PPIs in fact inhibit the vacuolar V-ATPase, and older studies nicely show that these pumps do indeed require much higher concentrations of PPIs compared to H + ,K + -ATPases [33,34]. V-ATPases are highly expressed in many cancers, including PDAC [35,36]. In mammalian cells, the most important cellular site for V-ATPase is in endocytotic and secretory granules.…”
Section: Discussionmentioning
confidence: 99%
“…In certain specialized cells performing significant acid/base transport, e.g., renal intercalated cells, epididymal cells, osteoclasts and phagocytes, V-ATPase also localizes to the plasma membrane [37]. Additionally, one study shows that in MCF-7 cancer cells the pump re-localizes from lysosomes to the plasma membrane following lysosomal exocytosis [38], but this does not seem to be the case in PDAC [36].…”
Section: Discussionmentioning
confidence: 99%